A new species of the genus Heteroderes (Coleoptera: Elateridae; Agrypninae) from Colombia - AGUIRRE-TAPIERO, MA. PILAR; GUZMÁN DE TOMÉ, MARTA E. (Revista Colombiana de Entomología, 2010)
A new species of click beetle, Heteroderes vallensis spec. nov. (Coleoptera: Elateridae, Agrypninae), is described from Valle del Cauca and Neiva, Colombia. Illustrations are provided of the holotype and the genitalia of both males and females.